Sodium nitrate regulates senescence accompanied by aortic atherosclerosis in ApoE−/− mice through the miR-34a/FGF-21 axis - Tao, Ning; He, Zhichao; Duan, Han; Wang, Liang; Yi, Jing; Shao, Jingyuan; Lv, Lin; Duan, Junzhao; Cao, Hu; Dong, Xiwen; Wang, Hua (Frontiers in Pharmacology, 2025)
IntroductionIncreasing evidence indicates that cellular senescence is a significant risk factor for atherosclerosis (AS).MethodsIn the present study, we used an apolipoprotein E knockout (ApoE−/−) mouse model to address the effect of sodium nitrate on senescence accompanied by atherosclerosis. After sodium nitrate intervention, the degree of AS pathological and cellular senescence changes was evaluated in mouse aortic. At the same time, an H2O2-induced human arterial endothelial cell (HAoEC) senescence model was established to verify the role of miR-34a in AS-associated senescence.ResultsWe observed that sodium nitrate decreased the Oil Red O-positive area, reduced the serum cholesterol (CHO) and triglyceride (TG) concentrations, and relieved inflammatory reactions in ApoE−/− mice. Moreover, the SA-β-Gal-positive area, the expression of cell cycle regulation-related genes and miR-34a in the aorta decreased after sodium nitrate treatment. Furthermore, sodium nitrate upregulated the expression of FGF21 by inhibiting the expression of miR-34a, thereby rescuing the senescent phenotype of HAoECs. These results suggested that sodium nitrate could rescue the endothelial cell senescence phenotype and alleviate aortic atherosclerosis in ApoE−/− mice by regulating the miR-34a/FGF21 axis.DiscussionThese findings might lead to the introduction of a new therapy for senescence-related diseases in the future.